Analysis Of Customer Understanding Of The Murabahah Contract Concept In Mitraguna Financing At Bank Syariah Indonesia, Langsa Branch: A Review Of Practice And Sharia Principles - Dayyan, Muhammad; Afni, Nurul; Yahya, Muhammad (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The development of Islamic banking in Aceh Province, particularly in Langsa City, is becoming increasingly competitive, highlighting the importance of public understanding as part of Islamic financial literacy. The purpose of this study is to analyze the understanding of the people of Langsa City regarding Mitraguna Bank Syariah Indonesia (BSI) financing products and their implications. The research used a descriptive qualitative method with data collection techniques through observation, structured interviews with 10 Mitraguna BSI customers in Langsa City who are payroll employees, and documentation studies. The results of the study reveal that the majority of informants interviewed were in the “Less Understanding” category regarding the sharia principles of BSI Mitraguna products. The factors causing this low level of understanding include a lack of in-depth socialization from the bank and a lack of background knowledge of sharia finance among customers. As a result, customers tend to focus on the ease of access and financial benefits of the product without paying attention to their understanding of the sharia contract and obligations attached to it. The research conclusion shows that there is a gap between product utilization and understanding of the accompanying sharia principles. Therefore, this study recommends the need for more effective education and communication strategies from BSI to improve customers' sharia financial literacy, thereby mitigating risks and ensuring the sustainability of healthy products.